Estimation of Household Equivalence Scales in a Model with Joint Determination of Commodity Demand and Labour Supply - Folkertsma, Carsten (Journal of Income Distribution®, 1995)
In this paper we present a method to estimate Barten-type equivalence scales in a single cross-section. Since the failure to identify the Barten-scales is due to the lack of commodity price variation in cross-sections, we use a model of joint determination of commodity demand and labour supply to solve the problem. The variation of wage rates is sufficient to identify the scales of commodities and leisure. We use this method to estimate Barten-type scales in an extended linear expenditure system on a Dutch expenditure survey.